Accidental presidents : [compact disc, unabridged] eight men who changed America - Cohen, Jared, 1981- (Simon & Schuster Audio, 2019)
Eight men have succeeded to the presidency when the incumbent died in office. In one way or another, each vastly changed our history. Only Theodore Roosevelt would have been elected in his own right. Only TR, Truman, and LBJ were re-elected. This book seeks to aid our understanding of the power and limits of the American presidency in critical times.